What is ax + z = aw − y , for a?

- anonymous

What is ax + z = aw − y , for a?

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- Astrophysics

You can do the following \[z+y=aw-ax\] notice I added y on both sides and subtracted ax from both sides, now you can factor out an a.

- Astrophysics

Any idea how?

- anonymous

No

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

Well yes

- Astrophysics

\[z+y=a(w-x)\] Notice since the left side both share an a

- Astrophysics

right side*

- anonymous

But how did you get z+y

- anonymous

and not -y-z

- Astrophysics

Oh I added +y instead of subtracting both sides by z just to make it look cleaner

- anonymous

But is subtracting both sides by z okay

- Astrophysics

Does that make sense? |dw:1444601291806:dw|

- Astrophysics

Yup, that's fine!

- Astrophysics

With what you did, you should get \[ax-aw=-z-y\]

- anonymous

but I got a = -y-z/x-w

- anonymous

is that right?

- Astrophysics

Yes!

- anonymous

really?!

- anonymous

it's not a = y+z/x-w

- Astrophysics

\[ax-aw=-z-y \implies a(x-w) = -z-y \implies a = \frac{ -z-y }{ x-w }\] that's perfect :)

- anonymous

??

- anonymous

How?

- Astrophysics

\[a = \frac{ -z-y }{ x-w }\] or \[a = \frac{ z+y }{ w-x }\] notice if you multiply the first equation by -1 you get the second equation, try to convince yourself by trying it

- anonymous

Do 2 negatives always = a positive in algebra?

- Astrophysics

yes :)

- anonymous

Even if they are not side by side

- anonymous

?

- Astrophysics

What do you mean

- anonymous

like -5-5

- anonymous

or is it only for variables?

- Astrophysics

Oh there you're just adding -(5+5) = -(10) = -10

- Astrophysics

Or subtracting by -5 how ever you like

- Astrophysics

-5-5 = -10

- anonymous

yeah

- Astrophysics

Unless you mean (-5)(-5) = 25

- anonymous

but how does -y-z = a positive?

- Astrophysics

-5x-5 = 25

- Astrophysics

(-y-z)*-1 = y+z

- anonymous

How did you get -1? Was it from factoring the two a's in the equation?

- Astrophysics

Oh no I was trying to show you that the first equation is same as the second, all you have to do is multiply by -1, algebra doesn't care :P
So the way I did your problem was basically the same way except I moved things differently, |dw:1444602003999:dw|

- anonymous

so it could come out either way and be right?

- Astrophysics

|dw:1444602123088:dw|

- Astrophysics

Yes

- Astrophysics

Now I'll do it again your way

- anonymous

k

- Astrophysics

|dw:1444602178558:dw|

- anonymous

Thank you so much!

- Astrophysics

Yw

Looking for something else?

Not the answer you are looking for? Search for more explanations.